Hydrogenation of Linoleic Acid by a Rumen Spirochete - Sachan, D. S. (1969)
Borrelia sp. B(2)5, when grown in a medium containing [1-(14)C] linoleic acid in an atmosphere of CO(2), was found to hydrogenate linoleic acid to trans-11-octadecenoic acid.